2003
DOI: 10.1046/j.1365-246x.2003.02036.x
|View full text |Cite
|
Sign up to set email alerts
|

Transition zone structure in a tectonically inactive area: 410 and 660 km discontinuity properties under the northern North Sea

Abstract: SUMMARY We report results from a year‐long deployment of broad‐band seismometers in Scotland to study the mantle structure in the northern United Kingdom. The region is tectonically inactive and its underlying mantle transition zone should not show unusual structure due to thermal perturbations caused by Cenozoic subduction or plume‐related volcanism. The estimated 410 and 660 km discontinuity depths, estimated by receiver function stacking, are 414 ± 5 and 655 ± 14 km, typical of average worldwide values. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 25 publications
3
8
0
Order By: Relevance
“…Furthermore, a hydrous MTZ has direct impact on the character of upper mantle discontinuities (Meijde et al, 2003). A receiver function study in the northern North Sea observed a significant weakening of the 660 km discontinuity (Helffrich et al, 2003), which was interpreted to be a consequence of a hydrated MTZ beneath the North Atlantic Ocean, an interpretation that is consistent with our images. Using body waveforms, Fuji et al (2010) found a low shear quality factor within the MTZ beneath the Northwestern Pacific, reminiscent of our vertical cross sections beneath the North Atlantic Ocean.…”
Section: Mtz Beneath the North Atlantic Oceansupporting
confidence: 89%
“…Furthermore, a hydrous MTZ has direct impact on the character of upper mantle discontinuities (Meijde et al, 2003). A receiver function study in the northern North Sea observed a significant weakening of the 660 km discontinuity (Helffrich et al, 2003), which was interpreted to be a consequence of a hydrated MTZ beneath the North Atlantic Ocean, an interpretation that is consistent with our images. Using body waveforms, Fuji et al (2010) found a low shear quality factor within the MTZ beneath the Northwestern Pacific, reminiscent of our vertical cross sections beneath the North Atlantic Ocean.…”
Section: Mtz Beneath the North Atlantic Oceansupporting
confidence: 89%
“…A normal transition zone thickness in agreement with the IASP91 global reference model was found in northern Eurasia by Mechie et al (1993) in wide-angle nuclear explosion data, in southern Germany by Kind and Vinnik (1988), below India by Saul et al (2000), at the Kola Peninsula by Dricker et al (1996), in the North Sea by Helffrich et al (2003), below the Arabian Shield by Benoit et al (2003), below the eastern Alps by Kummerow and Kind (2004), in southern Ireland by Landes et al (2006), and in central Tibet by Mechie et al (2011). Only small changes in the depth of the 410 in subduction zones have been found by Flanagan and Shearer (1998b).…”
Section: Other Regionssupporting
confidence: 72%
“…Another recent study proposed that the transition zone is richer in water than the mantle above and below [ Bercovici and Karato , 2003], a compositional change that should affect seismic velocities. Although, to a first order, the seismic properties of the main discontinuities do correspond to those of the olivine‐system phase transitions, it is still debated whether topography, width of the transitions and possibly even depth [ Irifune et al , 1998; Shim et al , 2001] agree in detail with these transitions [ Helffrich et al , 2003; Shearer , 2000; Xu et al , 2003]. Adding to this debate is the fact that it has long been recognized that the jump around 410 km in the most common seismic 1‐D models is less than that predicted for a pyrolitic mantle [ Katsura et al , 2004; Stixrude , 1997].…”
Section: Introductionmentioning
confidence: 99%